Incertezza: vite, marginalità e futuro ad Addis Abeba, Etiopia - Di Nunzio, Marco (L’Uomo società tradizione sviluppo, 2020)
Riassunto Questo articolo esamina l’incertezza dal punto di vista dei giovani emarginati nel centro di Addis Abeba. Partendo da una narrazione delle molteplici esperienze che hanno plasmato le traiettorie di questi giovani, esamino come e perché l’imprevedibilità del futuro sia vista non come un pericolo, ma come un modo per affrontare esperienze di marginalità ed esclusione. Con questa analisi, questo articolo mira a offrire un approccio aperto (open-ended) allo studio delle traiettorie di vita dei giovani in Africa, fornendo al contempo un resoconto etnografico di come l’incertezza diventi un terreno per agire e sperare. Embracing uncertainty: Young people on the move in Addis Ababa’s inner city This article examines uncertainty from the perspective of marginalized young men in Addis Abeba’s inner city. Starting from an appreciation of the multiple experiences that have shaped the trajectories of these young men, I examine how and why the fact of not knowing what is going to be next enabled them to navigate their condition of marginality and exclusion. For them, uncertainty was a state of possibility that they embraced as a ground for action and hope. This article aims to offer an open-ended approach to the study of life trajectories of young people in Africa, while providing an ethnographic account of how uncertainty is translated culturally, morally and through social practice into a sense of possibility.